2022
DOI: 10.4018/ijdai.301212
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Model for DDoS Attack Detection and Flash Event Management

Abstract: Distributed Denial of Service (DDoS) attacks are the foremost security concerns on the Internet. DDoS attacks and a similar occurrence called Flash Event (FE) signify anomalies in the normal network traffic, requiring intelligent interventions. This study presents the design and implementation of an intelligent model for the detection of application-layer DDoS attacks and the prevention of service degradations during FE. A Multi-Layer Perceptron (MLP) classifier was used for detecting DDoS attacks on applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The contributions were significant nevertheless the techniques could not identify FEs. The other studies as reported by ), Sun et al, (2019, and Tinubu et al (2022) proposed detection models that used the KOAD algorithm, KNN, and A Multi-Layer Perceptron (MLP) classifier respectively. Of the reviewed techniques, the authors attempted to develop models that could isolate the occurrence of either DDoS and/or FE whenever subjected to a specific attack.…”
Section: Results and Discussion Model Testing And Validationmentioning
confidence: 99%
“…The contributions were significant nevertheless the techniques could not identify FEs. The other studies as reported by ), Sun et al, (2019, and Tinubu et al (2022) proposed detection models that used the KOAD algorithm, KNN, and A Multi-Layer Perceptron (MLP) classifier respectively. Of the reviewed techniques, the authors attempted to develop models that could isolate the occurrence of either DDoS and/or FE whenever subjected to a specific attack.…”
Section: Results and Discussion Model Testing And Validationmentioning
confidence: 99%